Komitmen Pabrik Kelapa Sawit (PKS) Dalam Pengelolaan Lingkungan Hidup Bidang Fisik-Kimia di Kabupaten Muaro Jambi - Kurniawasyah Kurniawasyah; Guntar M Saragih (Universitas Batanghari Jambi, 2019)
The development of factories influences the quality of the environment, especially palm oil mills, in managing the need for checks on quality standards of environmental quality such as water quality, air quality and noise and quality of wastewater, which play an important role in the sustainable use of natural resources. submission of reports or compliance commitments from palm oil factories in conveying the quality standards of waste produced, from 20 palm oil mills operating in Muaro Jambi on average 90% have submitted periodic reports each semester in the management of environmental quality in terms of water quality, air and noise, and the quality of waste water has met the quality standard requirements in accordance with the Law of the Republic of Indonesia Number 32 of 2009 concerning Protection and Management of the Environment, using univariate analysis methods and application of calculations from SPSS obtained level k compliance from palm oil mills operating in compliance with the requirements in accordance with the quality standards and regulations that apply then in terms of PROPER assessment the average palm oil mill operating in Muaro Jambi Regency received a Gold rating in environmental management.